Guest Editorial - Al-Zoubi, A. Y. (International Journal of Interactive Mobile Technologies (iJIM), 2009)
This issue covers selected papers of the 4th "International Conference on Interactive Mobile and Computer aided Learning" - IMCL2009, April 2009, Amman, Jordan.